2021
DOI: 10.3390/cli9120173
|View full text |Cite
|
Sign up to set email alerts
|

Sea State Decadal Variability in the North Atlantic: A Review

Abstract: Long-term changes of wind-generated ocean waves have important consequences for marine engineering, coastal management, ship routing, and marine spatial planning. It is well-known that the multi-annual variability of wave parameters in the North Atlantic is tightly linked to natural fluctuations of the atmospheric circulation, such as the North Atlantic Oscillation. However, anthropogenic climate change is also expected to influence sea states over the long-term through the modification of atmospheric and ocea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 117 publications
(203 reference statements)
3
18
0
Order By: Relevance
“…A limitation of our study concerns the limited representation of the atmospheric multi-decadal variability in climate models. Indeed, a number of recent studies have shown that climate models significantly underestimate the amplitude of multi-decadal NAO, jet stream variability or sea surface temperature (Kim et al, 2018;Kravtsov, 2017;Sévellec & Drijfhout, 2019;Simpson et al, 2018). If the amplitude of the internal multi-decadal variability is in fact larger than simulated by climate models, the DoE for H s would occur even later than what was shown in this study (Figures 4 and 3).…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…A limitation of our study concerns the limited representation of the atmospheric multi-decadal variability in climate models. Indeed, a number of recent studies have shown that climate models significantly underestimate the amplitude of multi-decadal NAO, jet stream variability or sea surface temperature (Kim et al, 2018;Kravtsov, 2017;Sévellec & Drijfhout, 2019;Simpson et al, 2018). If the amplitude of the internal multi-decadal variability is in fact larger than simulated by climate models, the DoE for H s would occur even later than what was shown in this study (Figures 4 and 3).…”
Section: Discussionmentioning
confidence: 39%
“…This study focuses on the NA because it is a region of intense maritime traffic, numerous marine energy project and new engineering infrastructures that necessitates an accurate understanding of its wave climate variability. Moreover, numerous studies have demonstrated the link between the NA winter H s variability and the winter Sea Level Pressure (SLP) variability over the same region (Bacon & Carter, 1993; Dodet et al., 2010; Gulev et al., 1998; Hochet et al., 2021; Kushnir et al., 1997; Shimura et al., 2013; Woolf, 2002). In particular, a large part of the H s variability is believed to be correlated with the North Atlantic Oscillation (NAO) winter index (Woolf, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A number of approaches were used to understand the modulation of climate variability on ocean waves. These methods include linear regression (Kumar et al., 2016; Ramos et al., 2021), composite analysis (Kumar et al., 2019; Odériz et al., 2020; Ramos et al., 2021; Sasaki et al., 2021), EOF analysis (Hemer et al., 2010; Hochet et al., 2021; Izaguirre et al., 2011; Li et al., 2021; Ramos et al., 2021; Semedo et al., 2011; Stopa & Cheung, 2014), and wavelet analysis (Anoop et al., 2015; Castelle et al., 2018; Cromwell, 2006; Sasaki et al., 2021; Scott et al., 2021). Each of these approaches is briefly described below.…”
Section: Methodsmentioning
confidence: 99%
“…The cumulative variances of the first four EOFs account for 46.58% and 45.33% of the variability of H s anomalies in DJF and JJA, respectively. Note that the variances of the EOFs are domain‐dependent (Hochet et al., 2021). Researchers interested in a specific region should downsize the EOF domain and introduce extra significant climate indexes.…”
Section: Eof and Wavelet Analysismentioning
confidence: 99%
See 1 more Smart Citation